Evaluation of Range Condition and Trend of Ikwe Forest Reserve Igbor, Gwer-East Local Government Area of Benue State, Nigeria (2017)
Public concern over biological resources assessment has grown over the decade due to a decline in resources through habitat fragmentation. The study was designed to evaluate the range condition and trend of Ikwe Forest Reserve in Gwer-East local government area of Benue State, Nigeria. Assessment of herbaceous cover and composition, woody plant/shrubs density and plant vigor were carried out in randomly selected sample plots. Litter cover was determined by step point transect method, while erosion and its extent were assessed by presence and degree of gullies. Data collected was analyzed using descriptive statistics and analysis of variance (ANOVA). Results obtained showed that the herbaceous cover composed of perennials (39%) and annuals (61%).